Inovasi Alat Fiksasi Pada Pemeriksaan Radiografi Femur Proyeksi Lateral Cross Table(Sistematik Literature Review) - suwandi; Surdiyah Asriningrum (JURNAL TERAS KESEHATAN, 2026)
The cross-table lateral projection in femur radiography plays a crucial role in diagnosing lower limb trauma, particularly in critically ill patients who cannot be optimally repositioned. The main challenge in this procedure is maintaining limb stability to achieve optimal image quality while avoiding repeat exposures. Various fixation device innovations have been developed to enhance patient comfort, examination efficiency, and image quality. This study is a systematic literature review conducted using the PRISMA 2020 guidelines, with literature searches performed in PubMed, SpringerLink, and Google Scholar. Keywords included fixation device, cross-table lateral femur radiography, and trauma imaging. Out of 250 identified articles, 35 met the inclusion criteria and were thematically analyzed based on innovation type, design, materials, and clinical effectiveness. Results indicate innovation trends such as portable designs, adjustable modular systems, and the use of lightweight materials like aluminum and velcro straps. Clinically, these devices effectively reduce examination time, improve positional stability, enhance image quality, and minimize operator radiation exposure. In conclusion, innovative fixation devices significantly contribute to optimizing cross-table lateral femur radiography, with recommendations for further prototype development and direct clinical trials.